Structural Basis of VSIG3: The Ligand for VISTA - Xie, Xiaoxue; Chen, Caiping; Chen, Wenting; Jiang, Jingwei; Wang, Lanlan; Li, Tingting; Sun, Hongbin; Liu, Jun (Frontiers in Immunology, 2021)
B7 family members and their receptors play key roles in regulating T cell responses, and constitute very attractive targets for developing immunotherapeutic drugs. V-Set and Immunoglobulin domain containing 3 (VSIG3), a ligand for the novel B7 family immune checkpoint V-domain immunoglobulin suppressor of T cell activation (VISTA), can significantly inhibit T cell functions. Inhibitors targeting the VISTA/VSIG3 pathway are of great significance in tumor immunology. Here, we show the crystal structure of the extracellular domain (ECD) of the human VSIG3 protein at 2.64 angstrom resolution, and we produce recombinant human VSIG-3 ECD in both CHO cells and E. coli. Furthermore, we demonstrated the interaction of VISTA and VSIG3 by coimmunoprecipitation (Co-IP). Based on protein-protein docking for VISTA and VSIG3, we report a small molecule inhibitor of VSIG3 K284-3046 and evaluate its biological activities in vitro. This study was the first to reveal the crystal structure of VSIG3, and provides the structural basis for designing antibodies or compounds for the unique VSIG3/VISTA coinhibitory pathway in the treatment of cancers, autoimmune diseases and may be benificial of designing vaccines.